Pretty faces, marginal races: predicting election outcomes using trait assessments of British Parliamentary candidates - Mattes, Kyle; Milazzo, Caitlin (Elsevier, 2013)
The conventional wisdom on Western European politics leads us to believe that all the “action” lies with parties, because the unified parliamentary delegations in Western Europe draw voters’ attention to parties’ policies and images. Though British elections take place under a single member district plurality system, British parties, like their continental counterparts, are highly centralised and feature disciplined parliamentary delegations. Despite the strong ties between British candidates and their parties, we demonstrate that perceptions of candidates’ personal at-tributes can be used to predict general election outcomes. Using a computer-based survey where subjects are asked to evaluate real British candidates using only rapidly determined first impressions of facial images, we successfully predict outcomes from the 2010 general election. Moreover, we find that perceptions of candidates’ relative attractiveness are particularly useful for predicting outcomes in marginal constituencies.